Bimodal behavior in fabric drying kinetics: An interpretation of modes. Issue 23 (December 2019) - Hussan, Jagir R; Roberts, Paul; Hamilton, Maree; Gerneke, Dane; Hunter, Peter J
Thermo-physiological comfort is an essential property attributed to fabrics. Perceived comfort can be related to the delay in the user experiencing the ambient conditions and the manner in which the fabric manages liquid water. A multitude of material characteristics, ranging from the surface chemistry of the fibers, yarn packing and knit geometry, affect perceived comfort. Standard measures of thermal and evaporative resistance characterize the fabric response at steady state and do not provide insight into the thermal/vapor balance kinetics under dynamic conditions. While investigating an existing dynamic test, International Organization for Standardization 13029:2012, for relating fabric properties to comfort, we observed that the fabric drying kinetics exhibited bimodal behavior. Here, we describe the mechanism that leads to the observed bimodal drying kinetics. While the standard measures the time taken to reach steady state, we use the power profile of the modes to derive quantitative metrics to characterize fabric properties. The derived metrics are based on the observation that the heat of wetting is nearly a constant for a given relative humidity for a material, and that the heat of sorption per unit of absorbed water is identical for a wide range of fabrics. The derived metrics distinguish different fiber types and fabric geometries. The proposed metrics are easily calculated from experimental observations without requiring any modification to the standard test.